Functional characterization of HbRAR1 in Hevea brasiliensis reveals its role in the HSP90–SGT1–RAR1 complex during hypersensitive response - Liu, Qifeng; Wang, Jiali; Yu, Fei; Lu, Yiying; Zhang, Yu; Wang, Meng; Liang, Xiaoyu (Frontiers in Plant Science, 2026)
Powdery mildew is one of the most destructive foliar diseases of rubber tree (Hevea brasiliensis). To clarify the role of the conserved HSP90–SGT1–RAR1 molecular complex in rubber tree immunity, we identified and characterized two RAR1 homologs, HbRAR1–1 and HbRAR1-2. Both genes were significantly induced upon powdery mildew (Erysiphe quercicola) infection and were localized to the cytoplasm and nucleus. Yeast two-hybrid and bimolecular fluorescence complementation assays demonstrated that the HbRAR1 proteins interact with HbHSP90.1 and HbSGT1b via their two CHORD domains. Specifically, HbRAR1 binds the HATPase domain of HbHSP90.1 and the CS domain of HbSGT1b, forming a canonical HSP90–SGT1–RAR1 ternary complex. Additionally, Y2H, and BiFC assays confirmed that the core components of this complex, HbHSP90.1 and HbSGT1b, associate with the NLR immune receptor HbCNL4. Transient overexpression and electrolyte leakage assays indicate that co-expression of the HSP90–SGT1–RAR1 ternary complex with HbCNL4 enhances the hypersensitive response induced by HbCNL4. This study provides the first evidence in rubber tree that the HSP90–SGT1–RAR1 complex is structurally and functionally conserved and may play a central role in modulating NLR-triggered immune signaling. These findings offer key mechanistic insights into powdery mildew resistance and supply novel genetic resources for the cultivation of disease-resistant rubber tree cultivars.